Association of magnesium depletion score with serum anti-aging protein Klotho in the middle-aged and older populations - Zhuang, Zhijie; Huang, Shan; Xiong, Yingzhu; Peng, Yan; Cai, Shuangming (Frontiers in Nutrition, 2025)
BackgroundMagnesium deficiency and low levels of the anti-aging protein Klotho have been independently associated with various age-related diseases. The Magnesium Depletion Score (MDS) is recognized as a more valuable and reliable predictor of body magnesium status than traditional clinical markers such as serum and urine magnesium. However, the relationship between magnesium status and serum Klotho levels remains unexplored. This study aimed to investigate the association between magnesium depletion, as quantified by MDS, and serum Klotho levels in US adults.MethodsWe analyzed data from 11,387 participants aged 40–79 years in the National Health and Nutrition Examination Survey (NHANES) 2007–2016. Participants were divided into three groups based on MDS: low (0–1 points), middle (2 points), and high (3–5 points), reflecting cumulative risks of magnesium depletion derived from diuretic use, proton pump inhibitors, renal function, and alcohol intake. Serum Klotho levels were measured using a validated ELISA assay. Sample-weighted multivariable linear regression models were used to examine the association between MDS and serum Klotho levels, adjusting for age, sex, race, socioeconomic status, lifestyle factors (smoking, alcohol use), clinical parameters (body mass index, blood pressure, lipid levels), and energy intake.ResultsThe weighted average serum Klotho concentrations decreased significantly across MDS groups (low: 864.50, middle: 805.67, high: 755.02 pg./mL; p < 0.0001). After full adjustment, compared to the low MDS group, participants in the middle and high groups had significantly lower serum Klotho levels (β = −35.49, 95% CI: −62.29 to −8.69; β = −64.82, 95% CI: −115.30 to −14.34, respectively; p for trend = 0.003). This inverse association remained consistent across various subgroups, with particularly strong relationships observed in individuals with BMI <25, current smokers, and those with low income.ConclusionThis study provides novel evidence of an inverse association between MDS, a new valuable indicator of magnesium status, and serum Klotho levels in a large, representative sample of US adults. These findings suggest that monitoring magnesium status via MDS could help identify individuals at risk of accelerated aging, prompting interventions such as dietary adjustments or magnesium supplementation in high-risk populations. Further research is warranted to elucidate the mechanisms underlying this association and its implications for age-related diseases.